2021
DOI: 10.2478/mmcks-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of social media usage intensity in the financial sector of an emerging economy: a Pls-Sem Algorithm

Abstract: The purpose of this paper is to offer a critical understanding of the motivations and benefits of social media usage by small and medium financial enterprises with an empirical study from an emerging economy such as Ghana. Based on previous studies, the current study hypothesizes that customer-firm relationship, financial expectation, firm’s visibility and growth, and market share expectation drive social media usage intensity in the financial industry. Quantitative data was gathered from management and staff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 75 publications
(53 reference statements)
1
16
1
Order By: Relevance
“…Furthermore, social visibility allows a brand to reach a wide audience whilst also spending less time and effort doing so (Ju et al , 2021); it can also help to increase the return on investment, since the cost of advertising on these tools is generally lower (Ju et al , 2021). Moreover, it can mean the active transmission of the brand's identity (Aaker and Joachimsthaler, 2000), thus affecting consumers' perceptions of the brand (Pink et al , 2023), the brand's positioning in the market and favouring users that come across the brand's products (Amoah et al , 2021; Drèze and Zufryden, 2004). However, there is little research on brand social visibility in these new settings and no previous work was found in the context of beer brands (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, social visibility allows a brand to reach a wide audience whilst also spending less time and effort doing so (Ju et al , 2021); it can also help to increase the return on investment, since the cost of advertising on these tools is generally lower (Ju et al , 2021). Moreover, it can mean the active transmission of the brand's identity (Aaker and Joachimsthaler, 2000), thus affecting consumers' perceptions of the brand (Pink et al , 2023), the brand's positioning in the market and favouring users that come across the brand's products (Amoah et al , 2021; Drèze and Zufryden, 2004). However, there is little research on brand social visibility in these new settings and no previous work was found in the context of beer brands (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…A beer firm may have as many as 50 different Facebook pages, along with YouTube clips and YouTube channels and several tweets encouraging user traffic and facilitating the brand's social visibility (Lobstein et al , 2017; Pierce et al , 2022). In this sense, social visibility is the public exposure of the brand on SM and traffic is users' presence and interactions on the SM (Jiménez-Martínez and Edwards, 2023) and both traffic and social visibility can be encouraged by the contents generated (Amoah et al , 2021; Morra et al , 2018; van Tubergen et al , 2021; Vo Minh et al , 2022). Nevertheless, little research has been conducted to explore the correlation between the content generated, the SM traffic and the brand's social visibility.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of brand personality has gained significant attention in marketing and consumer behavior research over the years [1]. Brand personality refers to the human-like characteristics and traits attributed to brands, enabling consumers to perceive brands as having distinct personalities [2]. It is considered an essential element in building brand identity and connecting emotionally with consumers [3].…”
Section: Introduction 11 Background and Contextmentioning
confidence: 99%
“…Kaplan and Haenlein [2] defined social media as a group of Internet-based applications that build on the ideological and technological foundations of Web 2.0, and allow the creation and exchange of user-generated content". Moreover, the emergence of social media has improved communication and the sharing of ideas with others through various social media channels [3]. Today, the pandemic (Corona Virus Disease, COVID-19), has had severe consequences for businesses [4].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has established the association of social media usage with a firm's performance in the context of SMEs in developing countries [3,4,8,19]. Social media is pivotal to SMEs' development of communication strategies [21].…”
Section: Introductionmentioning
confidence: 99%